2007
DOI: 10.1007/s00221-007-1030-0
|View full text |Cite
|
Sign up to set email alerts
|

Voluntary modulation of human stretch reflexes

Abstract: It has been postulated that the central nervous system (CNS) can tune the mechanical behavior of a joint by altering reflex stiffness in a task-dependant manner. However, most of the evidence supporting this hypothesis has come from the analysis of H-reflexes or electromyogram (EMG) responses. Changes in overall stiffness have been documented but, as yet, there is no direct evidence that the CNS can control reflex stiffness independently of the intrinsic stiffness. We have used a novel identification algorithm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
48
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(50 citation statements)
references
References 55 publications
1
48
1
Order By: Relevance
“…Stretch reXexes strongly inXuence the EMG at initial ground contact by providing muscular stiVness (HoVer and Andreassen 1981;Ludvig et al 2007). ReXexes can be classiWed according to their latencies and subsequently according to the diVerent neural circuits they are mediated by.…”
Section: Neuromuscular Parameters Characterizing Ssc Movementsmentioning
confidence: 99%
“…Stretch reXexes strongly inXuence the EMG at initial ground contact by providing muscular stiVness (HoVer and Andreassen 1981;Ludvig et al 2007). ReXexes can be classiWed according to their latencies and subsequently according to the diVerent neural circuits they are mediated by.…”
Section: Neuromuscular Parameters Characterizing Ssc Movementsmentioning
confidence: 99%
“…It has been investigated for a wide range of muscles at the elbow (Colebatch et al 1979;Crago et al 1976;Evarts and Granit 1976;Hagbarth 1967;Rothwell et al 1980), wrist (Calancie and Bawa 1985;Jaeger et al 1982;Lee and Tatton 1982), finger (Capaday and Stein 1987;Marsden et al 1981;Rothwell et al 1980), ankle Agarwal 1979, 1980;Ludvig et al 2007), and jaw (Pearce et al 2003). The bottom panel is the corresponding muscle activity, which shows modulation in the long-latency stretch response (LL) but not the short-latency stretch response (SL).…”
Section: Task Dependency Of Stretch Responsesmentioning
confidence: 98%
“…He found that, although the verbal instruction did not modulate the short-latency stretch response (i.e., 25-50 ms postperturbation onset), the magnitude of the long-latency stretch response was larger when participants were instructed to resist the perturbation. Since this seminal work, similar patterns of goal-dependent modulation have been shown in many muscles, including those acting at the jaw (Johansson et al 2014), shoulder (Kurtzer et al 2014;Nashed et al 2012;Omrani et al 2013;Pruszynski et al 2008), elbow (Cluff and Scott 2013;Colebatch et al 1979;Crago et al 1976;Evarts and Granit 1976;Nashed et al 2012Nashed et al , 2014Omrani et al 2013;Pruszynski et al 2008Pruszynski et al , 2011bRavichandran et al 2013;Rothwell et al 1980;Shemmell et al 2009), wrist (Calancie andBawa 1985;Jaeger et al 1982; Lee and Tatton 1982;Manning et al 2012), finger (Capaday and Stein 1987;Cole et al 1984;Marsden et al 1981), and ankle (Gottlieb and Agarwal 1979;Ludvig et al 2007). …”
mentioning
confidence: 99%